Youth Board of Cyprus Scholarship - Kassianos, Angelos P. (My University, 2026)
Scholarship by the Youth Board of Cyprus to perform a study on ‘Using online patient simulations to improve the clinical reasoning skills of medical and nursing students in Cyprus’.
Keywords: Education